2017
DOI: 10.1002/jaba.405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating increased effort for item disposal to improve recycling at a university

Abstract: An evaluation of increased response effort to dispose of items was conducted to improve recycling at a university. Signs prompting individuals to recycle and notifying them of the location of trash and recycling receptacles were posted in each phase. During the intervention, trashcans were removed from the classrooms, and one large trashcan was available in the hallway next to the recycling receptacles. Results showed that correct recycling increased, and trash left in classrooms increased initially during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…Picture exchanges increased, and the effect could have been a result of reduced effort, but could have also been due to an increased delay to reinforcement in the high distance condition. Finally, some authors (i.e., Fritz et al, 2017;Ludwig et al, 1998;O'Connor et al, 2010) manipulated the number and /or location of recycling bins to increase recycling. Although the reduced effort to recycle could have been responsible for the increase in recycling, the increased number or change in location of bins could have served as a prompt to recycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Picture exchanges increased, and the effect could have been a result of reduced effort, but could have also been due to an increased delay to reinforcement in the high distance condition. Finally, some authors (i.e., Fritz et al, 2017;Ludwig et al, 1998;O'Connor et al, 2010) manipulated the number and /or location of recycling bins to increase recycling. Although the reduced effort to recycle could have been responsible for the increase in recycling, the increased number or change in location of bins could have served as a prompt to recycle.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Fritz et al (2017) further investigated the effects of response effort on recycling, but rather than adding recycling bins, these researchers removed trashcans from classrooms and placed them in the same location as the recycling bins. Following trashcan removal, the percentage of correct recycling increased, and this procedure was less expensive than adding recycling bins.…”
Section: Manipulation Of Proximitymentioning
confidence: 99%
“…In this context, the effect of prompts should be considered. Fritz et al (2017) showed that signs prompting recycling can increase recycling behavior even when decreasing the proximity of the bins. Therefore, offering glasses without straws as a default option with the separately offered straws in a box, and provided with prompts that inform about the impact of straw consumption, might be an effective strategy to significantly lower straw consumption and lower the discontent about missing straws as reported by Wagner and Toews (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the intervention is introduced while repeated measurement of the dependent variables continues. To demonstrate functional control of the effects attributable to the intervention (as opposed to some other factor), a return to the nointervention condition may be arranged (as in a reversal design; e.g., Fritz et al, 2017), or the staggered application of the intervention may be arranged for another community or community sector (as in a multiple-baseline design; e.g., Clayton & Nesnidol, 2017). The latter is the most flexible because it permits refinement of the independent variable across staggered applications.…”
Section: Experimental Evaluation Of Community Interventionsmentioning
confidence: 99%